PENGARUH LAYANAN KONSELING KELOMPOK TERHADAP MOTIVASI BELAJAR SISWA DI SMP PAHLAWAN NASIONAL - Mujahid, Tamimi; Azzahra, Aliyyah Putri (Effect : Jurnal Kajian Konseling, 2025)
This study aims to analyze the influence of group counseling services on students' learning motivation at SMP Pahlawan Nasional. The method used is a quasi-experimental design with control and experimental groups. The research sample consisted of ninth-grade students selected based on the recommendation of the guidance counselor due to their low learning motivation. Data were obtained through questionnaires filled out before (pre-test) and after (post-test) the treatment. The research results show a significant increase in students' learning motivation after participating in group counseling services. The average learning motivation score increased from 55.91% (low category) to 68.70% (high category) with an average increase of 12.78%. Statistical analysis using the Wilcoxon test reinforces these results, showing that group counseling services significantly influence the increase in students' learning motivation (p < 0.05). This research makes an important contribution to the field of education, particularly in the use of group counseling services as an effective method to enhance students' learning motivation. This is relevant to be applied to students with low learning motivation in order to improve their academic performance.